Interactions between N-acetyl-l-cysteine protected CdTe quantum dots and doxorubicin through spectroscopic method. (June 2015) - Yang, Xiupei; Lin, Jia; Liao, Xiulin; Zong, Yingying; Gao, Huanhuan
Graphical abstract: Highlights: CdTe quantum dots with the diameter of 3–5 nm were synthesized in aqueous solution. The modified CdTe quantum dots showed well fluorescence properties. The interaction between the CdTe quantum dots and doxorubicin (DR) was investigated. Abstract: N -acetyl-l -cysteine protected cadmium telluride quantum dots with a diameter of 3–5 nm were synthesized in aqueous solution. The interaction between N -acetyl-l -cysteine/cadmium telluride quantum dots and doxorubicin was investigated by ultraviolet–visible absorption and fluorescence spectroscopy at physiological conditions (pH 7.2, 37 °C). The results indicate that electron transfer has occurred between N -acetyl-l -cysteine/cadmium telluride quantum dots and doxorubicin under light illumination. The quantum dots react readily with doxorubicin to form a N -acetyl-l -cysteine/cadmium telluride-quantum dots/doxorubicin complex via electrostatic attraction between the NH3 + moiety of doxorubicin and the COO − moiety of N -acetyl-l -cysteine/cadmium telluride quantum dots. The interaction of N -acetyl-l -cysteine/cadmium telluride-quantum dots/doxorubicin complex with bovine serum albumin was studied as well, showing that the complex might induce the conformation change of bovine serum due to changes in microenvironment of bovine serum.